Pengaruh Pupuk Hayati Terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq.) pada Pembibitan Awal - Muh Yusuf Indris; Irwan Halid; Sukriming Sapareng (Indonesian Journal of Fundamental Sciences, 2019)
This study aims to determine the effectiveness of N2-fixing microbes contained in organic organic fertilizers at four levels of nitrogen fertilizer application in increasing the performance of oil palm seedlings. The experiment was carried out in the form of an experiment using a Randomized Block Design with 2 factors: organic organic fertilizer and nitrogen fertilizer. The first factor with three levels of treatment, namely without organic biological fertilizer, Organic fertilizer from cow dung (Agro Flower) 1 g / kg of Soil and Organic organic fertilizer (Biost) 1 g / kg of Soil. While the second factor consists of four levels, namely without N fertilizer, N fertilizer 50% of the standard dose, N fertilizer 100% of the standard dose, and N fertilizer of 150% of the standard dose. Each treatment was tested on 4 oil palm seedlings and repeated 3 times, so that 144 experimental plants were obtained. The observations made were the variable plant performance includes plant height, number of leaves, and stem diameter. Variants of plant nutrient levels included total N nutrient levels, P nutrient levels, and K nutrient levels. The results showed that N-inhibiting microbes contained in organic organic fertilizer increased plant height and stem diameter significantly in oil palm nurseries. The use of a 100% dose of N fertilizer together with organic biofertilizers shows the best crop performance results.